Managing urban growth in South Africa : challenges and constraints - Selemela, A.; Ngoepe, R. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
The purpose of this paper is to investigate the relationship between urban growth and urbanization to show how their incorporation adversely affects urban development. Urban development in South Africa was affected by the Apartheid era whereby much attention was given to urban areas and after 1994 many people started moving from rural to urban areas which led to massive urbanisation levels especially in Gauteng province. The more population increases in urban areas it requires the need for urban development planning to accommodate the increasing population. Subsequently urban growth poses many problems, some of which are caused by the expansion of the population and some due to the physical expansion of the towns. The major problem includes provision of services, employment, pollution, traffic congestion and urban sprawl. Although there are policies which have been implemented by the government to promote equitable urban development, still increasing urban growth and high levels of urbanisation levels remain a challenge to urban development. It is in this context that this paper argues that unplanned urbanisation interrupts effective urban development in South Africa. Furthermore, the paper emphasises on understanding urbanisation and urban growth which requires considerate variety of factors that can affect the city functionality and sustainability. Thus, the paper concludes that failure to curb urbanisation levels and urban growth in South Africa’s cities is an indication of inadequate urban development planning. Therefore, the paper recommends that urban development planning measures such as strategies for growth management, assessing urban settlement sizes and evaluating urban sprawl should be enhanced to maintain a balanced urban morphology.
Journal article published in the 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Overcrowding; Urban Growth; Urban Sprawl; Urbanisation; Cities and towns -- Growth; Urbanization -- South Africa; Community development, Urban